PENERAPAN PSAK 45 DALAM PENYUSUNAN LAPORAN KEUANGAN ORGANISASI KEMAHASISWAAN DI LINGKUNGAN FKIP UNTAN PONTIANAK - Heni Kuswanti (JURKAMI : Jurnal Pendidikan Ekonomi, 2021)
Student organizations are places for students to gather who have common goals. Every organization must have a work program that will be planned and achieved during the period of its management. The work program will be able to run with sufficient funding, so that each organization must have a source of financing that can support the achievement of organizational goals. Funding in student organizations must be accounted for in accordance with the applicable regulations. This study aims to determine how the application of the Statement of Financial Accounting Standards Number 45 in the preparation of financial reports of student organizations in the FKIP Untan. The method used is a descriptive method with a survey form. Data collected in the form of qualitative data from interview and quantitative data in the form of financial reports of student organizations which were analyzed using qualitative descriptive analysis. The results showed that the student organizations within FKIP Untan had not yet prepared financial reports based on the Statement of Financial Accounting Standards Number 45. This was evidenced by the incompatibility of the types and methods of preparing reports that had been made with the regulations regarding the financial statements of non-profit organizationsAbstrak: Organisasi kemahasiswaan merupakan wadah berkumpulnya mahasiswa yang memiliki tujuan bersama. Setiap organisasi pasti memiliki program kerja yang akan di rencanakan dan dicapai selama periode kepengurusannya. Program kerja akan dapat dijalankan dengan pembiayaan yang cukup, sehingga setiap organisasi pasti memiliki sumber pembiayaan yang dapat mendukung pencapaian tujuan organisasi. Pembiayaan dalam organisasi kemahasiswaan harus dapat dipertanggungjawabkan sesuai peraturan yang telah berlaku. Penelitian ini bertujuan untuk mengetahui bagaimana penerapan PSAK 45 dalam penyusunan laporan keuangan organisasi kemahasiswaan di lingkungan FKIP Untan. Metode yang digunakan adalah metode deskriptif dengan bentuk survei. Data yang dikumpulkan berupa data kualitatif hasil wawancara dan data kuantitatif berupa laporan keuangan organisasi kemahasiswaan yang dianalisis dengan analisis deksriptif kualitatif. Hasil penelitian menunjukkan bahwa organisasi kemahasiswaan di lingkungan FKIP Untan belum melakukan penyusunan laporan keuangan berdasarkan PSAK 45. Hal ini dibuktikan dengan tidak sesuainya jenis dan cara penyusunan laporan yang sudah dibuat dengan aturan mengenai laporan keuangan organisasi nirlaba